2005
DOI: 10.1002/mnfr.200400084
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin alleviates activities of intestinal and renal disaccharidases in streptozotocin-induced diabetic rats

Abstract: Specific activities of both intestinal and renal dissacharidases, such as sucrase, maltase, and lactase, were altered in diabetic rats. Our study was focused to evaluate the effect of feeding quercetin - a bioflavanoid on intestinal and renal dissacharidases in streptozotocin-induced diabetic rats. The rats were fed with 0.1% quercetin in diet. A reduction in intestinal maltase and sucrase, activities in quercetin-fed diabetic rats was observed in contrast to the increased activities in the starch-fed diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…Protective effects of quercetin in diabetes mellitus and DN have also been reported in rat models (12)(13)(14). Our data showed that quercetin treatment at 40 µM led to smaller cells with irregular shapes, larger gaps between adjacent cells, and weakened cell adhesion (Fig.…”
Section: Effects Of Quercetin On Morphology and Proliferation In Highsupporting
confidence: 77%
See 1 more Smart Citation
“…Protective effects of quercetin in diabetes mellitus and DN have also been reported in rat models (12)(13)(14). Our data showed that quercetin treatment at 40 µM led to smaller cells with irregular shapes, larger gaps between adjacent cells, and weakened cell adhesion (Fig.…”
Section: Effects Of Quercetin On Morphology and Proliferation In Highsupporting
confidence: 77%
“…Protective effects of quercetin in diabetes mellitus and DN have also been reported in rat models (10)(11)(12). In addition, the protective effects of quercetin have been observed in a streptozotocin (STZ)-induced model of diabetes mellitus (11)(12)(13)(14). Furthermore, Kim et al (15) reported that dietary quercetin attenuated fasting and postprandial hyperglycemia.…”
Section: Introductionmentioning
confidence: 92%
“…43,16 Moreover, some studies have shown that polyphenolic compounds may reduce the activity of endogenous enzymes in the small intestine and thereby may influence the regulation of blood glucose levels. 22,46 In summary, the present experiment demonstrated that some of the positive changes in the cecal metabolism of rats that resulted from the ingestion of a diet enriched only with FOS were suppressed or slightly suppressed by the addition of an ET strawberry extract. The pH value, SCFA production, and β-glucuronidase activity in the cecum of rats fed with FOS were affected upon the addition of the ET strawberry extract.…”
Section: ■ Discussionmentioning
confidence: 81%
“…Chronic consumption of QE (0.1% of diet) decreased blood glucose in STZ-treated rats [6,7]. QE protected pancreatic β cells from oxidative stress and damage, resulting in increased insulin secretion in STZ-treated rats [5].…”
Section: Discussionmentioning
confidence: 99%